2010
DOI: 10.1016/j.cancergencyto.2010.07.128
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of chronic lymphocytic leukemia cells with CpG oligodeoxynucleotide gives consistent karyotypic results among laboratories: a CLL Research Consortium (CRC) Study

Abstract: Cytogenetic abnormalities in CLL are important prognostic indicators. Historically, only interphase cytogenetics was clinically useful in CLL because traditional mitogens are not effective mitotic stimulants. Recently, CpG-oligodeoxynucleotide (ODN) stimulation has shown effectiveness in CLL. The CLL Research Consortium (CRC) tested the effectiveness and reproducibility of CpG-ODN stimulation to detect chromosomally abnormal clones by five laboratories. More clonal abnormalities were observed after culture of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 26 publications
0
32
0
1
Order By: Relevance
“…In brief, 0.8 2 1.0.mL of specimen was added to each of two, 5.0 mL of MarrowMax media (Life Technologies, Carlsbad, CA) replicate cultures and stimulated with a B-cell cocktail consisting of: 100lL CpG-ODN-GNKG685 (10 lg/mL, Sigma, St Louis, MO), 50 lL Pokeweed mitogen (PWM) from Phytolacca americana (10 lg/mL, Sigma, St Louis, MO) and 100 lL Phorbol 12-myristate 13-acetate (PMA) (40 ng/mL, Sigma, St Louis, MO), as previously described [15]. The cells were cultured at 378C and 5% CO 2 for 3-days, and harvested/banded according to standard procedures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, 0.8 2 1.0.mL of specimen was added to each of two, 5.0 mL of MarrowMax media (Life Technologies, Carlsbad, CA) replicate cultures and stimulated with a B-cell cocktail consisting of: 100lL CpG-ODN-GNKG685 (10 lg/mL, Sigma, St Louis, MO), 50 lL Pokeweed mitogen (PWM) from Phytolacca americana (10 lg/mL, Sigma, St Louis, MO) and 100 lL Phorbol 12-myristate 13-acetate (PMA) (40 ng/mL, Sigma, St Louis, MO), as previously described [15]. The cells were cultured at 378C and 5% CO 2 for 3-days, and harvested/banded according to standard procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it does not permit the detection of novel cytogenetic aberrations. The emergence of CpG-ODN-oligonucleotides (CpG-ODN), a potent B-cell mitogen, has enhanced our ability to reproducibly detect clonal cytogenetic aberrations by karyotyping, expanding our understanding of clinically relevant cytogenetic aberrations [15][16][17][18]. Array-based profiling and, more recently, next-generation sequencing have identified recurrent genomic imbalances [19] and highlighted the importance of subclonal genomic lesions (i.e., intratumoral heterogeneity) [20].…”
Section: Introductionmentioning
confidence: 99%
“…11,12 A prospective study conducted by the CLL Research Consortium confirmed that abnormal clones in CLL are more readily detected with CpG oligonucleotide stimulation than with traditional B-cell mitogens; moreover, the clonal abnormalities revealed by CpG stimulated metaphase cytogenetics are consistent with that detected by interphase FISH and are reproducible among different cytogenetic laboratories. 13 However, the use of CpG stimulation for CLL cytogenetics is not yet universally available.…”
Section: Diagnosismentioning
confidence: 99%
“…• 6.3.3.1 CMA analysis can add valuable information that will support and supplement both G-banded chromosome analysis and FISH. It can detect small cryptic clinically significant copy number changes (CNCs) in various hematological neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…31 CLL cell stimulation in culture using CpGoligonucleotides greatly improves the detection rate of clonal cytogenetic abnormalities by G-banded chromosome analysis. 6,7 -To assign the patient into clinically relevant prognostic subgroups, the following panel of FISH probes is recommended: a. ATM (11q22.3) probe b. Centromeric probe for chromosome 12: for trisomy 12 c. 13q14.3 probe (including D13S319) d. TP53 (17p13.1) probe -FISH can also be useful for the differential diagnosis with mantle cell lymphoma (MCL), for which FISH using the IGH-CCND1 fusion probes is recommended. -In CLL, CMA analysis has proven to be very effective in detecting CNCs and cnLOH at genomic regions with established prognostic significance, and it provides a much higher resolution compared to G-banded chromosome and FISH analyses.…”
Section: Chronic Lymphocytic Leukemiamentioning
confidence: 99%